Some indicators of a state of health of preschool aged children of Irkutsk - E. A. Tkachuk (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Modern society implies a shift of public relations from industrial to post-industrial or information society. In the conditions of post-industrial society the training system unprecedentedly extends, information loading that demands reconsideration of influence of informatization on health of children (as in background (or public), and an educational mode) and development of new hygienic requirements to a mode of educational institutions repeatedly increases. In research, on the example of preschool educational institutions of Irkutsk in the conditions of change of level of informatization of society in the temporary period from 1998 to 2012, changes in physical development and intellectual efficiency of children are revealed. In total 174 children, 96 children in 1998 and 78 children in 2012 aged from 5,5 till 6,5 years of two preschool educational institutions are investigated: 82 children in the 1st preschool institution and 92 children in the 2nd preschool institution. The obtained data testify to increase in anthropometrical indicators of children of the senior group in 2012 in comparison with children visiting preschool educational institutions in 1998. Also in research it is shown that for children of the senior groups of the preschool institutions located in the central region of Irkutsk, gratsilization and detseleration processes aren>t characteristic. However, some distinctions of anthropometrical indicators of children of the studied preschool educational institutions demand additional hygienic studying. Research of intellectual working capacity in Anfilov>s test revealed that the efficiency indicator from 1998 for 2012 statistically significantly didn>t change. Despite it statistically significant increase in quantity of mistakes (from 1,5 to 2,3 times in comparison with 1998) and quantities of the seen lines (from 3,9 to 9,8 times in comparison with 1998) (р < 0,05) is noted that testifies to increase in speed and decrease in quality of information processing of children at the present stage of development of society.